INTERFERENSI PENGGUNAAN NAMA DIRI BERBAHASA ARAB DI INDONESIA (Sebuah Kajian Sosiolinguistik) - Ubaidillah Ubaidillah (Adabiyyāt: Jurnal Bahasa dan Sastra, 2011)
A Proper noun is a lexeme that is used to name persons, places, and certain objects. There are many proper nouns within Arabic lexemes which are used in Indonesian personal names. However, there are interferences of Indonesian language in the use of the proper nouns. This paper aims to describe several of those interferences and the influencing factors. The method used in this research is the method of translational equality because this analysis concerns two different languages. The result of the analysis shows that differences of phonological system of Arabic language and Indonesian language influence these interferences. For example, Hanif is pronounced Kanif; Munif is pronounced Munip; Rofa'i is pronounced Rofangi, etc. In addition, lack of understanding in using Arabic original phonemes in some communities influences the transliteration of the Arabic to the Latin letters.